2004
DOI: 10.1097/00002030-200406180-00007
|View full text |Cite
|
Sign up to set email alerts
|

Atazanavir enhances saquinavir hard-gel concentrations in a ritonavir-boosted once-daily regimen

Abstract: The addition of atazanavir to saquinavir/ritonavir increased saquinavir Ctrough, Cmax and AUC0-24 by 112, 42 and 60%. Ritonavir Cmax and AUCo-24 increased by 34 and 41%. The regimen was well tolerated, with no significant change in laboratory parameters, except for the occurrence of hyperbilirubinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 8 publications
5
39
0
1
Order By: Relevance
“…This can be a further limitation as differences in boosted protease inhibitor exposure have been seen between HIV-positive and -negative individuals (9), suggesting that patients with HIV infection may have lower plasma concentrations than those measured in our study. However, when our findings are compared to the concentrations of both darunavir and atazanavir measured in previously published studies (historical controls), the concentrations are similar to those observed in HIV-positive subjects (3,5,18).…”
Section: Vol 55 2011 Protease Inhibitor Concentration Persistence 4221supporting
confidence: 85%
“…This can be a further limitation as differences in boosted protease inhibitor exposure have been seen between HIV-positive and -negative individuals (9), suggesting that patients with HIV infection may have lower plasma concentrations than those measured in our study. However, when our findings are compared to the concentrations of both darunavir and atazanavir measured in previously published studies (historical controls), the concentrations are similar to those observed in HIV-positive subjects (3,5,18).…”
Section: Vol 55 2011 Protease Inhibitor Concentration Persistence 4221supporting
confidence: 85%
“…Plasma concentrations of ATV, SQV, and RTV were determined by validated high-pressure liquid chromatography-tandem mass spectrometry methods (equipment from Merck-Hitachi, Germany, and Applied Biosystems/Canada at Therapia GmbH, Berlin, Germany) that are described elsewhere (28). The reliable lower limit of quantification was 20 ng/ml, and the linearity of the calibration curve for all tested compounds was proved up to 20,000 ng/ml (3,28).…”
Section: Patientsmentioning
confidence: 99%
“…32 The best virological response at 48 weeks was found in the ATV 400 mg od group (41%) over the ATV 600 mg od (29%) or SQV/r groups (35%), and there were fewer adverse event discontinuations in the ATV/SQV groups than in those in the SQV/r arm. Salvage therapy refers to ARV regimens devised to reduce viral replication in treatment-experienced patients with virological failure on a prior regimen.…”
Section: Atv In Arv-experienced Patientsmentioning
confidence: 87%